2021
DOI: 10.3390/nano11102647
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat Transfer Enhancement in a Triple Tube Latent Heat Storage System Using Circular Fins with Inline and Staggered Arrangements

Abstract: Inherent fluctuations in the availability of energy from renewables, particularly solar, remain a substantial impediment to their widespread deployment worldwide. Employing phase-change materials (PCMs) as media, saving energy for later consumption, offers a promising solution for overcoming the problem. However, the heat conductivities of most PCMs are limited, which severely limits the energy storage potential of these materials. This study suggests employing circular fins with staggered distribution to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The HTF is circulated in the inner pipe in the opposite direction of gravity, while it is circulated in the gravity direction inside of the outer pipe. As established in the literature [ 42 , 43 ], such a configuration provides superior performance when compared to co-current directions for the fluid flow. As a result, the flow of HTF through the PCM casing is kept as counter-current.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The HTF is circulated in the inner pipe in the opposite direction of gravity, while it is circulated in the gravity direction inside of the outer pipe. As established in the literature [ 42 , 43 ], such a configuration provides superior performance when compared to co-current directions for the fluid flow. As a result, the flow of HTF through the PCM casing is kept as counter-current.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Recently, the research interest regarding latent heat thermal energy storage (LHTES) increased due to the high thermal efficiency and low phase change temperature point; however, the thermal conductivity of the PCM is generally poor and inappropriate for many applications [15][16][17]. Accordingly, various techniques have been modelled to improve the heat transfer efficiency of the PCM during the charging and discharging methods [18].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that installing this type of fin with a downward–upward pattern can raise the melting rate by up to 88%. Sun et al [ 12 ] employed inline and staggered arrangements of circular fins to improve the rate of the phase change process. They discovered that the staggered distribution of fins can improve the melting and heat charging rate by 37.2 and 59.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%